WACANA POS-DRAMATIK DALAM TEATER POOH-POOH SOMATIC: ON CROWD OF BIOGRAPHIESKARYA KALANARI THEATER MOVEMENT YOGYAKARTA - Cantini, Cucum (TAMUMATRA, 2018)
The Pooh-pooh Somatic: On Crowd of Biographies that Kalanari Teater Movement has performed at Pusat Kebudayaan Koesnadi Hardjasoematri, Gadjah Mada University on August 22 2017, has become one of the dramatic theater movement of discourse to the post-dramatic. The phenomenon of the death of the text has come to the fore in Indonesian performing arts. This review will discuss the discourse of drama production by reaching out the Lehmann post-dramatic phenomenon. The death of conventional texts that are present in the drama-script, turns into a phenomenon of the emergence of theater productions that put the body forward rather than the language that was previously the main standard to convey meaning to the audience. Through Foucalt's perspective of discourse, this study will discuss the process of dramatic theater movement from dramatic to post-dramatic. The point of this paper is that post-dramatic theater becomes part of the performing arts that remains part of contemporary drama or theater. While not exploiting text or language, symbols and sounds have been communicated to the audience. In this case, the narration through symbols and sounds is agreed as a universal language.Keywords: drama, post-dramatic, language, theater, Kalanari.